African land tenure: the options for more efficient regulation - Biaou, Gauthier (Technical Centre for Agricultural and Rural Cooperation, 1993)
Gauthier Biaou, an agronomist, was in charge of agricultural extension in Benin before taking up his present position as deputy head of the Department of Rural Economy and Sociology at the Faculty of Agricultural Sciences. The traditional land...